The incidence of mesothelioma has not decreased for the last twenty years in Southeast region of Anatolia - Carkanat, AI (Makerere Medical School, 2011)
BACKGROUND: Malignant pleural Mesothelioma (MPM) is a very rarely encountered tumor in the normal population. OBJECTIVES: To investigate the variations in incidence of MPM in Southeast region of Turkey. METHODS: We retrospectively investigated the data of 161 MPM patients who were diagnosed from January 2000 to December 2009. The residential areas were determined according to asbestos exposure which plays a role in MPM etiology; previously reported as having asbestos (Region 1) and asbestos has not been determined previously (Region 2). RESULTS: One hundred nine (109) of the patients (67.7%) included from the Region 1 and 52 of them (32.3%) included from the Region 2. MPM incidence of the last decade was 3.9/100,000 person/year for the whole region. In Region 1, 2000–2004 incidences was 12.6/100,000 person/year and 2005–2009 incidences was 14.9/100,000 person/year. In Region 2, 2000–2004 incidences was 0.4/100,000 person/year and 2005–2009 incidences was 1.0/100,000 person/year. According to the recently conducted incidence studies in our region, MPM incidence increased in region 1 and decreased in region 2. The number of patients applying to our hospital has increased in the last three years. CONCLUSION: This increase, in Region 1 may be associated with continuous use of asbestos.